Prevalence and geographical distribution of Usher syndrome in Germany - Spandau, Ulrich; Rohrschneider, Klaus (Graefe's archive for clinical and experimental ophthalmology, 2002)
Purpose:To estimate the prevalence of Usher syndrome in Heidelberg and Mannheim and to map its geographical distribution in Germany.
Gesehen am 02.03.2021